Growth, biochemical indices and transcriptomic profile of Chinese mitten crab (Eriocheir sinensis) respond to different ratios of dietary carbohydrates to lipids - Zuo, Rantao; Wen, Bin; Jiang, Yusheng; Huang, Shu; Yi, Qilin (Frontiers in Marine Science, 2023)
Introduction Although carbohydrates and lipids are important energy substances for Chinese mitten crab (Eriocheir sinensis), little is known about their synergistic effect on the growth, energy utilization characteristics and mechanisms involved in this process. Methods A 58-d feeding experiment was conducted to investigate the effects of dietary carbohydrate to lipid ratio (C/L) on the growth performance, biochemical indices, and metabolism-related differential gene expression of juvenile E. sinensis in both intermolt (InM) and premolt (PrM) stages. Five experimental diets were formulated with increasing dietary C/L (1.34, 2.39, 3.59, 5.52 and 9.42). Results The results showed that the weight growth rate of juvenile E. sinensis was highest in dietary C/L3.59 group, which was significantly higher than that in the other groups. As dietary C/L increased, the hepatic glycogen contents increased, but triglyceride contents decreased in the hepatopancreas of E. sinensis in the InM. In both two molting stages, the activities of glycogen synthase and fatty acid synthase paralleled with their contents, respectively. Crabs in the InM showed higher contents of triglyceride and the activities of glycolytic rate-limiting enzymes but lower contents of hepatic glycogen than those in the PrM, especially in the C/L 1.34 and C/L 3.59 groups. In all dietary groups, the activities and transcription of gluconeogenesis and fatty acid synthesis related enzymes were significantly higher in the InM than those in the PrM. KEGG analysis showed that differential genes were enriched in fatty acid biosynthesis, fatty acid metabolism, oxidative phosphorylation pathway, pentose phosphate pathway, pyruvate metabolism and steroid biosynthesis between different dietary groups and molting stages. Discussion To conclude, the optimal dietary C/L was estimated to be 3.59 for juvenile E. sinensis based on the survival and growth performance. Compared to PrM, E. sinensis in the InM was more active in the carbohydrate metabolism (glycolysis and gluconeogenesis) and fatty acid synthesis, with more triglyceride and less glycogen accumulated in the hepatopancreas.This study could contribute to better understanding the carbohydrate and lipid metabolism between different molting stages, and optimizing the precise feed formulation for juvenile E. sinensis.